Complete muscle-sparing technique in axillary closure of atrial septal defects. (December 2013) - Gil-Jaurena, Juan-Miguel; Castillo, Rafael; González, Mayte
Minimally invasive cardiac surgery is gaining wide acceptance. The midaxillary approach hides the incision under the right arm. Concerns may arise regarding functional recovery should the latissimus dorsi and serratus anterior muscles be affected by this maneuver. A modified technique that spares both muscles, without splitting their fibers, is described. Six patients have been operated on, with excellent functional and cosmetic results, and no side-effects.